Peran Guru PAI dalam Mengajarkan Akhlak di Media Sosial - Syafaatunnisa, Shopiah; Nurulhaq, Dadan (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
The problem of ethics is becoming increasingly complex over time. The phenomenon of netizens who lack manners, the prevalence of hoaxes, and other violations of ethics are so vulnerable to occur on social media. Social media users who are mostly students are prone to being unstable and need reinforcement and guidance in order to use social media wisely. The emergence of social media has caused an urgent need for the dual role of PAI teachers to teach ethics that are not only applied in real interactions but also in virtual ones. This study is a qualitative research using a literature review method. The results of this study indicate that the role of PAI teachers is very important and crucial in teaching ethics on social media like facebook, instagram, and others that are commonly used by students. This role consists of exemplary and teaching roles. The exemplary role requires PAI teachers to be role models in social media. Meanwhile, the teaching role requires PAI teachers to explain the teaching materials with ethical content in a more contextual way that touches all aspects of ethics in both real and virtual interactions.